2021
DOI: 10.3389/fpsyg.2021.539799
|View full text |Cite
|
Sign up to set email alerts
|

Putting Stress in Historical Context: Why It Is Important That Being Stressed Out Was Not a Way to Be a Person 2,000 Years Ago

Abstract: It was not until the middle of the twentieth century that scientists and Western societies began to label the combination of physiological and psychological responses that people display when things are getting too much and out of balance as “stress.” However, stress is commonly understood as a universal mechanism that exists across times and cultures. In a certain sense, this universality claim is correct: the physiological and endocrinological mechanisms underlying the stress response are not a modern invent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…The detrimental effects of stress can be found anecdotally throughout human history; encountering wild animals, enemies, natural catastrophes, etc. [ 17 , 35 ]. For instance, it has been suggested that King Saul in the Bible displayed “well-known signs of depression” characteristic of job insecurity stress [ 36 ], presumably resulting from the self-generated pressure of losing his kingship to a more popular David.…”
Section: A Brief History Of Stress Researchmentioning
confidence: 99%
“…The detrimental effects of stress can be found anecdotally throughout human history; encountering wild animals, enemies, natural catastrophes, etc. [ 17 , 35 ]. For instance, it has been suggested that King Saul in the Bible displayed “well-known signs of depression” characteristic of job insecurity stress [ 36 ], presumably resulting from the self-generated pressure of losing his kingship to a more popular David.…”
Section: A Brief History Of Stress Researchmentioning
confidence: 99%
“…As the discussion of Jüttemann's approach has made clear, historical psychology can only thrive as an interdisciplinary endeavor that is willing to take up impulses from neighboring fields of research such as cognitive archeology, historical anthropology, and cultural history. Although there are already some publications by psychologists on topics such as memory (Danziger, 2008), stress (Hutmacher, 2019(Hutmacher, , 2021, or personhood (Danziger, 2012; see also Smith, 2005) that could be considered genuinely psychological contributions, psychology still needs to find its own, unique voice. That is, it remains to be determined what constitutes the particularity of the psychologists' perspective on the historicity of the human psyche.…”
Section: Conclusion: the Future Of Historical Psychologymentioning
confidence: 99%
“…Stress often originates from the outside. Furthermore, "adverse or demanding circumstances" are entirely subjective and likely to affect different people in different ways [108,109]. Any change can have potential for eliciting a stress response, even if personally perceived as having positive utility.…”
Section: Stressmentioning
confidence: 99%